2016
DOI: 10.1063/1.4963111
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric properties of skutterudite CoSb3 thin films

Abstract: The thermoelectric properties of Co-Sb thin films with different Sb content and with a thickness of 30 nm were investigated with respect to the composition and the corresponding structural properties of these films. The films were prepared by molecular beam deposition either by codeposition on heated substrates or room temperature deposition followed by a post-annealing step. It was found that the prepared films exhibit bipolar conduction, indicated by a positive Hall constant and a negative Seebeck coefficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…All samples crystallized in the body centred cubic space group Im 3 (#204). As obtained aer renement, the unit cell volume was 73.87 nm 3 . The Co metal ions are located at the 8c sites (1/4, 1/4, 1/ 4), while the pnictogen atom Sb occupied the 24g sites (0, y, z).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…All samples crystallized in the body centred cubic space group Im 3 (#204). As obtained aer renement, the unit cell volume was 73.87 nm 3 . The Co metal ions are located at the 8c sites (1/4, 1/4, 1/ 4), while the pnictogen atom Sb occupied the 24g sites (0, y, z).…”
Section: Resultsmentioning
confidence: 82%
“…2 The enhancement in zT can be done either by increasing the power factor S 2 /r or by decreasing k. CoSb 3 is a low band gap skutterudite compound semiconductor with high S and high carrier mobility. 3 It has a cubic structure with the formula of MX 3 , where M is a metal ion, such as Co, Rh, and Ir, and X is any metalloid (such as As and Sb). Of the eight subcubes in a cubic unit cell, two cubes are voids that can accommodate guest atoms and rattle inside.…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in κ is mainly due to the fact that the high-density nano-interfaces in the low dimensional materials enhance significantly the scattering of electrons and phonons. In the past ten years, TE properties of CoSb 3 materials have been improved significantly by the nanocrystallization of CoSb 3 -based materials [124][125][126][127][128][129][130][131][132][133][134][135][136][137][138][139][140] or the preparation of thin film materials [141][142][143][144][145][146][147]. Toprak et al [125] reported a novel chemical alloying method to prepare CoSb 3 materials with different nanoparticle sizes.…”
Section: Optimization At Atomic-molecular Scalementioning
confidence: 99%
“…20 Therefore, many studies on the synthesis of high performance thin films, including CoSb 3 films, have been investigated. [21][22][23][24][25][26] For example, A. Ahmed et al 27 obtained a power factor of 7.92 mW m K −2 for the CoSb 2 -containing mixed phase thin film and 1.26 mW m K −2 for the stoichiometric CoSb 3 thin film. However, TE properties of CoSb 3 thin films remain lower than those of bulk materials due to the difficulty of controlling precisely the composition of the thin films.…”
Section: Introductionmentioning
confidence: 99%